Soil biological properties as influenced by organic nutrient management in soybean (Glycine max) - YADAV, M K; PUROHIT, H S; SHARMA, S K; JAT, G; YADAV, S K; MEENA, S C; MEENA, R H; JAIN, H K (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was carried out to study the soil microbial dynamics and enzyme activities as influenced by organic nutrients management in soybean [Glycine max (L.) Merr.] under Typic Haplustepts soil of Rajasthan. The experiment comprised 12 treatment combinations of organic source of nutrients, i. e. control (T1), 100% RDF (T2), 100% FYM (T3), 100% vermicompost (T4), 100% compost (T5), 100% green-leaf manure (T6), 50% FYM + 50% vermicompost (T7), 50% FYM + 50% compost (T8), 50% FYM + 50% green-leaf manure (T9), 50% vermicompost + 50% compost (T10), 50% vermicompost + 50% green leaf manure (T11) and 50% compost + 50% green-leaf manure (T12). The experiment was laid out in a randomized block design with four replications. The soil microbial population (bacterial, fungal, actinomycetes) at 30 DAS, 60 DAS, dehydrogenase activity and alkaline phosphatase activity of soil significantly influenced due to organic nutrient fertilization, viz. 100% vermicompost treatment (T4) in pooled analysis. However, the application of 100% vermicompost (T4) on bacterial population, fungal population, actinomycetes population of soil at 30 DAS and 60 DAS was found statistically at par with the application of 50% FYM + 50% vermicompost (T7), 50% FYM + 50% compost (T8), 50% vermicompost + 50% compost (T10) and 50% vermicompost + 50% green-leaf manure (T11) in pooled analysis.